L'adattamento delle città ai cambiamenti climatici Urban Adaptation to Climate Change - Carlo Gerundo (TRIA Urban Studies, 2018)
Cities and all the activities carried out in an urban environment significantly influence climate change causes but, at the same time, they are greatly affected by them. For these reasons, urban areas not only represent one of the problems, but also the main field of application of intervention strategies to be developed in order to mitigate the negative effects of climate change. Among the strategies to contrast climate change, the adaptation to its environmental effects has been pushed right into the background in scientific debate, mainly due to the difficulty experienced in transferring urban climatology into methods that can be easily implemented by planners to draw up land use plan. This volume is an attempt to strengthen the cultural background of urban planner, establishing solid connections with urban climatology, in order to build a new language, able to consider the relationships between urban morphology and climate change adaptation strategies to be implemented.